Relaxation dynamics associated with the multiple polymorphic phase transitions in morphotropic phase boundaries BiScO3-PbTiO3 solid solutions. (1st January 2021) - Jaffari, G. Hassnain; Zafar, Adeel; Ali, Wajid; Yuan, Guoliang
Abstract: High temperature electrical properties of morphotropic phase boundary BiScO3 -PbTiO3 compositions, exhibiting high piezoelectric coefficient, saturation polarization, field induced strain and low dielectric loss have been presented in detail. Dielectric loss and various electrical parameters have been comprehensively utilized to identify multiple dipolar relaxation dynamics in the regime where conductivity effects are low. Dielectric data confirms presence of various polymorphs exhibiting lower (higher) symmetry configuration, which extends to wider (narrower) temperature regime. Effect of conductivity associated with the charge transport is not dominant up to 600 K, which shows that this material is a promising candidate for high temperature applications. Graphical abstract: Image, graphical abstract